An imatinib-only window followed by imatinib and chemotherapy for Philadelphia chromosome-positive acute leukemia: long-term results of the CMLALL1 trial. Issue 3 (March 2015) - Lickliter, Jason D.; Taylor, Kerry; Szer, Jeff; Grigg, Andrew; Arthur, Christopher; Hughes, Timothy P.; Durrant, Simon; Filshie, Robin; Irving, Ian; Seldon, Michael; Ellacott, Jennifer; Boyd, Andrew W.; et al.
Abstract: We report long-term results in 40 patients with Philadlephia chromosome-positive (Ph+) acute leukemia who received an imatinib monotherapy window to evaluate in vivo effects on BCR–ABL signaling prior to induction chemotherapy. The first 25 patients (cohort 1) received the LALA-94 protocol without further imatinib (newly diagnosed Ph+ acute lymphoblastic leukemia [ALL]) or induction chemotherapy followed by single-agent imatinib. Subsequent patients (cohort 2) continued imatinib concurrently with either LALA-94 (newly diagnosed Ph + ALL) or other intensive chemotherapy regimens. Cohort 2 had a complete response (CR) rate of 93% and 5-year survival of 69%. For newly diagnosed Ph+ ALL, survival was superior in cohort 2 compared with cohort 1. Toxicity was similar to that expected for chemotherapy alone. Among 10 evaluable patients, rapid loss of phospho-CRKL occurred during the imatinib window in seven patients (all achieved CR) and incomplete inhibition in three patients (none with CR). In summary, a pharmacodynamic window design permitted biomarker assessment of BCR–ABL targeting without compromising clinical outcomes.